Karl Barth’s unnatural exegesis: an inquiry into Barth’s biblical interpretation with special reference to Christ and Adam - Howey, Matthew S. (2004)
This thesis is an enquiry into the problem of Barth’s unnatural exegesis. Previous attempts to account for the distinctiveness or strangeness of Barth’s exegesis have emphasised its theological character or its context in Church dogmatic tradition. This thesis judges this approach inadequate; in place of theological or dogmatic principles, this thesis searches for a basic hermeneutical principle which will render Barth’s exegesis intelligible and constructive.